مقتضى العطف وفلسفته في الدرس النحوي: دراسة في أثره وتطبيقاته - محمود، سامح محمد عبدالمحسن (جامعة الأزهر - كلية اللغة العربية بالمنصورة, 2022)
الحمد لله، والصلاة والسلام على رسول الله، وعلى آله وصحبه ومن ولاه، أما بعد،، فقد كانت قواعد العطف وضوابطه العامة ومقتضياته اللازمة ذات أثر واضح في الدرس النحوي، لاسيما مسائل الخلاف في كثير من أبواب النحو المختلفة، لذا صح أن يطلق عليها مصطلح فلسفة، فأحصى البحث مقتضيات العطف، وبينها، وتتبع أثرها في الدرس النحوي، مع توضيح خلاف النحويين في إقرار بعضها، وكان من نتائج هذه الدراسة: أ- أنه كان لفلسفة العطف أثر بالغ في التأويل النحوي في الأبواب المختلفة، وقد أكد البحث أنه لم تكن تأويلات النحويين لبعض النصوص اعتباطا. ب- لم تكن المقتضيات التسع محل اتفاق بين النحويين، بل اختلفوا في إقرار بعضها. ج- أنه كان لهذه الفلسفة أثر واضح في تضعيف بعض آراء النحويين، واختياراتهم. د- استدل النحويون بلازم العطف على صحة مذاهبهم، وفي نقد وتضعيف آراء المخالف، كما كانت معضدة لاستشهاد بعضهم ببعض الشواهد الشعرية. Thank goodness, prayer and peace for our Adnan prophet, and for His God and His Blessed Companion, either after The rules of kindness and its general controls had a clear impact on the grammatical lesson, whether in rulings, reasoning, weighting, or choosing from issues of disagreement in many different sections of grammar So I called it the term philosophy, so I counted these philosophies, explained them, traced their impact in the grammar lesson, and divided the research according to these philosophies, So he came in nine demands, each one of which is specific to a statement of one of these philosophies, while showing its impact in the different sections of grammar, preceded by the preface of its title: (The Philosophy of Kindness and Measurement) In it, she explained the meaning of kindness, linguistically and idiomatically, and the relationship of the philosophy of kindness to analogy: A- That the philosophies of kindness had a profound effect on the grammatical interpretation of the various chapters. B- The nine philosophies were not in agreement among the grammarians, but rather they differed in approving some of them. C- That these philosophies had a clear impact on weakening some of the grammarians’ opinions and choices. And the last thing they said is, thank God, God.
Keywords: النحو العربي -- القواعد النحوية -- فلسفة العطف -- الآراء النحوية -- الشواهد الشعرية